2017
DOI: 10.1016/j.ajog.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Condom use and incident sexually transmitted infection after initiation of long-acting reversible contraception

Abstract: Background: Use of more effective contraception may lead to less condom use and increased incidence of sexually transmitted infection. Objective: The objective of this study was to compare changes in condom use and incidence of sexually transmitted infection acquisition among new initiators of long-acting reversible contraceptives to those initiating non-long acting reversible contraceptive methods. Study Design: This is a secondary analysis of the Contraceptive CHOICE Project. We included two sample popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 20 publications
(40 reference statements)
0
31
0
Order By: Relevance
“…32 While condoms are the best way to prevent STD transmission, these are often not used in longer term relationships. 9,33 Australian guidelines recommend that sexually active people younger than 30 be screened for STDs regularly (and more often if an individual is engaging in sexual activities that increase transmission risk); 34 heightened efforts to encourage men and women to visit their general practitioner for regular sexual health checkups are needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 While condoms are the best way to prevent STD transmission, these are often not used in longer term relationships. 9,33 Australian guidelines recommend that sexually active people younger than 30 be screened for STDs regularly (and more often if an individual is engaging in sexual activities that increase transmission risk); 34 heightened efforts to encourage men and women to visit their general practitioner for regular sexual health checkups are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Australian clinic users aged 16-24, fewer than one-third of hormonal contraceptive users reported consistent use of condoms, and dual method use decreased as relationship length increased. 9 Using condoms by themselves or as a supplementary method in new or casual relationships (and a decline in condom use as relationship length increases) has also been found in the United States. 9,10 The use of condoms in combination with another method by Australian women is an important area of research, particularly given the country' s increasing STD rates among women.…”
Section: Young Women's Complex Patterns Of Contraceptive Use: Findingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another analysis of a cohort of CHOICE participants revealed that women using LARC were less likely to use a condom every time with every partner (5.2% vs. 11.3% in non-LARC users), but that the condom use patterns did not change over the year after initiating a LARC method. [15] Similarly, a recent randomized controlled trial evaluating the effect of initiation a contraceptive implant on condom use did not find any difference in condom use before compared to after implant insertion, or when comparing women who received immediate vs. delayed implant insertion. [16] These findings suggest that it may not be initiation of the LARC method itself that impacts condom use, but that other factors related to LARC use may also impact condom use.…”
Section: Discussionmentioning
confidence: 99%
“…Another analysis of a cohort of CHOICE participants revealed that LARC users did have higher rates of STI (3.9% vs. 2.0% in non-LARC users), but this was not attributable to a decrease in condom use after LARC initiation. [15] One previous study suggested that lower condom use among implant users compared to pill users did not confer a greater risk of STIs due to more stable sexual relationships among implant users. [20] Conversely, another study evaluating high school adolescents found that LARC users were 60% less likely to use condoms, and also more likely to have a greater number of sexual partners, putting them at increased risk for STIs.…”
Section: Discussionmentioning
confidence: 99%